THE EFFECT OF REMUNERATION AND MOTIVATION ON EMPLOYEE PERFORMANCE AT STATE UNIVERSITY OF MAKASSAR - Syamsurijal Basri; Sri Hastuti; Andi Ratu Ayuashari Anwar; Nanang Hermawan (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to analyze the effect of remuneration and motivation on employee performance at Makassar State University (UNM). This research uses a quantitative approach with a survey method. The population consisted of all UNM employees with a random sampling technique, involving 109 respondents. The research instrument was a Likert-scale questionnaire analyzed using multiple linear regression via SPSS version 26. The results show that remuneration and motivation have a positive and significant effect on employee performance, both partially and simultaneously. The coefficient of determination (R²) of 0.360 indicates that 36% of employee performance variation is explained by remuneration and motivation. Thus, implementing a fair remuneration system and effective motivation strategies can improve employee productivity and performance at UNM